Pneumothorax after minimally invasive plate osteosynthesis for midshaft clavicle fracture: A case report. Issue 33 (August 2019) - Kim, Mi Kyeong; Lee, Hyun-Jung; You, Ann Hee; Kang, Hee Yong
Abstract: Rationale: Isolated fracture of clavicle is usually treated with nonoperative conservative treatment. However, surgical treatment, customized for individual patient's need, is increasingly done. With regard to the surgery of the clavicle fracture, pneumothorax is a possible, but rare complication. Patient concerns: We report the case of a 32-year-old healthy female patient who underwent minimally invasive plate osteosynthesis (MIPO) due to a clavicle fracture. To avoid direct exposure of fracture site, the pre-contoured plate was inserted through the lateral incisional port to reach the medial incisional port. There was no problem during the surgery, but the patient complained of dyspnea in the post-anesthesia care unit. Diagnoses: A chest radiograph was taken immediately, and a definitive finding of pneumothorax was revealed. Interventions: A tube was inserted at the right chest. Outcomes: The patient's dyspnea was resolved. On the 6th day after the surgery, the chest radiograph revealed that pneumothorax was nearly resolved, enabling to remove the chest tube. On the 9th day after the surgery, the patient was discharged without complication. Lessons: After clavicle surgery requiring strong dissection like MIPO, the possibility of pneumothorax is suspected and the patient should be carefully observed.